2023
DOI: 10.1101/2023.01.27.525870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complexity of spatiotemporal plantar pressure patterns during everyday behaviours

Abstract: The human foot sole is the primary interface with the external world during balance and walking, and also provides important tactile information on the state of contact. However, prior stud- ies on plantar pressure have focused mostly on summary metrics such as overall force or centre of pressure under limited condi- tions. Here, we recorded spatiotemporal plantar pressure pat- terns with high spatial resolution while participants completed a wide range of daily activities, including balancing, locomotion, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…We demonstrated that localized skin ischemia on the foot sole of a healthy individual generates significant changes to skin sensitivity. As hypothesized, this change in skin sensitivity was localized to high pressure foot regions (Cleland et al, 2023) and coincided with locations where blood flow was drastically reduced during loading (3MT and heel). The Mean ± SD of PORH Peak for each site across the foot sole for a 15% body weight load (light gray) or a 50% body weight (dark gray) load.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…We demonstrated that localized skin ischemia on the foot sole of a healthy individual generates significant changes to skin sensitivity. As hypothesized, this change in skin sensitivity was localized to high pressure foot regions (Cleland et al, 2023) and coincided with locations where blood flow was drastically reduced during loading (3MT and heel). The Mean ± SD of PORH Peak for each site across the foot sole for a 15% body weight load (light gray) or a 50% body weight (dark gray) load.…”
Section: Discussionsupporting
confidence: 56%
“…We demonstrated that localized skin ischemia on the foot sole of a healthy individual generates significant changes to skin sensitivity. As hypothesized, this change in skin sensitivity was localized to high pressure foot regions ( Cleland et al, 2023 ) and coincided with locations where blood flow was drastically reduced during loading (3MT and heel). The sensitivity of the medial arch, which experiences very little plantar pressure during stance-like loading, did not generate a PORH response, and did not experience any significant changes to skin sensitivity.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The force applied to a surface is especially important when judging roughness (Hollins and Risner, 2000;Lederman and Taylor, 1972), with higher forces leading to greater roughness ratings (Lederman and Taylor, 1972;. As the foot regularly experiences forces exceeding three times body mass (Cleland et al, 2023;McKay et al, 2017), materials may be perceived as much rougher at the foot sole than at the hand. Investigating texture perception on the foot sole is important, because textures might provide important clues about the stability of a given surface.…”
Section: Introductionmentioning
confidence: 99%